2004
DOI: 10.1002/adma.200306624
|View full text |Cite
|
Sign up to set email alerts
|

How Polycrystalline Devices Can Outperform Single‐Crystal Ones: Thin Film CdTe/CdS Solar Cells

Abstract: Grain boundaries (GBs) participate in the photovoltaic energy conversion process in polycrystalline solar cells as efficient photocurrent collectors and transporters, as shown by high‐ resolution characterization of CdTe GBs in CdTe/CdS cells (see Figure). This suggests that structural defects can be advantageous for device performance, if properly designed, even in devices whose operation is based on physics of ideal, perfect solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 32 publications
6
122
1
2
Order By: Relevance
“…3). This finding suggests that the grain boundaries do not contain significant depletion regions and that the electrical current is uniformly photo-generated in the bulk and at the interfaces of the ARTICLE grains, a situation quite different from that of CdTe but somewhat akin to that found for CIGS cells 22,23 . This may be the result of a low density of surface states, possibly due to the partial organic nature of this semiconductor, with the organic moieties passivating the surface (amines are well-known passivation agents for II-VI semiconductor surfaces).…”
Section: Resultsmentioning
confidence: 71%
“…3). This finding suggests that the grain boundaries do not contain significant depletion regions and that the electrical current is uniformly photo-generated in the bulk and at the interfaces of the ARTICLE grains, a situation quite different from that of CdTe but somewhat akin to that found for CIGS cells 22,23 . This may be the result of a low density of surface states, possibly due to the partial organic nature of this semiconductor, with the organic moieties passivating the surface (amines are well-known passivation agents for II-VI semiconductor surfaces).…”
Section: Resultsmentioning
confidence: 71%
“…From the experimental evidence it appears that type inversion applies rather to CdTe solar cells 4,5 whereas in CIGS ͑Refs. 7-9, 12, 16, and 17͒ the band bending around the GB is relatively small.…”
Section: E Collection Of Carriers Along Grain Boundariesmentioning
confidence: 99%
“…Work by Seger et al 28 and others [53][54][55] has shown that higher charge-collection efficiency in photovoltaics can be achieved with single crystal semiconductors compared to polycrystalline material due to reduced recombination as a result of fewer grain boundaries and surface defects. This nding extends to PEC water-splitting, which also involves the separation of photogenerated charges in semiconductors under illumination.…”
Section: Passivation Layer Suppression Of Surface Recombination and Imentioning
confidence: 99%